Loss of Rubicon ameliorates doxorubicin-induced cardiotoxicity through enhancement of mitochondrial quality. (1st December 2019) - Liu, Xiaoyun; Zhang, Shasha; An, Lin; Wu, Jian; Hu, Xiaowen; Lai, Shuaiwei; Mazhar, Haniya; Zou, Yunzeng; He, Lin; Zhu, Hongxin
Abstract: Background: The therapeutic potential of doxorubicin (DOX) is limited by cardiotoxicity. Rubicon is an inhibitory interacting partner of autophagy protein UVRAG. Currently, the role of Rubicon in DOX-induced cardiotoxicity is unknown. In this study, we test the hypothesis that loss of Rubicon attenuates DOX-induced cardiotoxicity. Methods: A mouse model of acute DOX-induced cardiotoxicity was established by a single intraperitoneal injection of DOX at a dose of 20 mg/kg. Rubicon expression was detected by Western blot. Cardiac damage was determined by measuring activities of lactate dehydrogenase and myocardial muscle creatine kinase in the serum, cytoplasmic vacuolization, collagen deposition, ROS levels, ATP content and mitochondrial damage in the heart. Cardiac morphometry and function were assessed by echocardiography. Markers for autophagy, mitophagy and mitochondrial dynamics were evaluated by Western blot and real time reverse transcription polymerase chain reaction. Results: Rubicon expression was reduced in the heart 16 h after DOX treatment. DOX induced accumulation of cytoplasmic vacuolization and collagen, increased serum activities of lactate dehydrogenase and myocardial muscle creatine kinase, enhanced ROS levels, reduced ATP content, pronounced mitochondrial damage and greater left ventricular wall thickness in wild type mice, which were mitigated by Rubicon deficiency. Mechanistically, loss of Rubicon improved DOX-induced impairment of autophagic flux, Parkin-mediated mitophagy and mitochondrial fission and fusion in the heart. Conclusions: Loss of Rubicon ameliorates DOX-induced cardiotoxicity through enhancement of mitochondrial quality by improving autophagic flux, mitophagy and mitochondrial dynamics. Rubicon is a potential molecular target for prevention and therapy of DOX cardiotoxicity. Highlights: Loss of Rubicon ameliorates DOX-induced cardiotoxicity. DOX-induced mitochondrial damage in the heart is attenuated by Rubicon deficiency. Loss of Rubicon mitigates DOX-induced impairment of autophagic flux, mitophagy and mitochondrial dynamics in the heart.